The Ethics of Communication to Parents in Surah Maryam Verse 42-48: Study on Kitab Tafsir Al-Taysir By Firanda Andirja - Fatih Muhammad (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
Filial piety is a noble duty of a child to his parents as a form of respect and affection. There are many ways to show filial piety, including good communication. Good communication is the key to portraying a child's respect and expressing affection for parents. This research is a qualitative method to analyze primary data sources, namely Tafsir al-Taysir which is then analyzed with other data in the form of previous research which is then processed in the form of descriptions. The results of the study of Surah Maryam verses 41-48 in Tafsir al-Taysir by Firanda Andirja explain that the ethics of communicating to parents in the verse is centered on verbal communication. The verbal communication ethics consist of using a good call, gentle speech (qaulan layyina), concise but clear speech (qaulan baligha), and explaining the various positive and negative effects of an action (mau'idzah).